Circulating adhesion molecules in obstructive sleep apnea and cardiovascular disease - Pak, Victoria M. (2013)
Over 20 years of evidence indicates a strong association between obstructive sleep apnea (OSA) and cardiovascular disease. Although inflammatory processes have been heavily implicated as an important link between the two, the mechanism for this has not been conclusively established. Atherosclerosis may be one of the mechanisms linking OSA to cardiovascular morbidity. This review addresses the role of circulating adhesion molecules in patients with OSA, and how these may be part of the link between cardiovascular disease and OSA. There is evidence for the role of adhesion molecules in cardiovascular disease risk. Some studies, albeit with small sample sizes, also show higher levels of adhesion molecules in patients with OSA compared to controls. There are also studies that show that levels of adhesion molecules diminish with continuous positive airway pressure therapy. Limitations of these studies include small sample sizes, cross-sectional sampling, and inconsistent control for confounding variables known to influence adhesion molecule levels. There are potential novel therapies to reduce circulating adhesion molecules in patients with OSA to diminish cardiovascular disease. Understanding the role of cell adhesion molecules generated in OSA will help elucidate one mechanistic link to cardiovascular disease in patients with OSA.